Electromagnetic processes in the pulsed inductors of electron accelerators - Чемерис, В. Т.; Бородій, І. О. (Proceedings of National Aviation University (archive), 2013)
The process of magnetic field setting up at its excitation in the cross section of the closed laminated core of the pulsed inductor has been investigated by numerical methods. Analysis of the field expansion from the boundaries of cross section to its center was realized due to using of two-dimensional numerical model of the wave equation written in non-dimensional form with application of equivalent magnetic μ and dielectric ε parameters. Two situations had been taken into consideration: 1) the medium of laminated package has anisotropic ideal magneto-dielectric properties (no electrical conductivity); 2) the medium of package is isotropic, but has the losses of energy due to electrical conductivity of ferromagnetic layers. The ratio of the basic velocity (which defines via basic dimension of the package cross section and duration of the pulsed field) to the speed of electromagnetic wave propagation in this medium serves as characteristic parameter of similarity for the processes in models with different scale of time and/or dimensions. The magnetic Reynolds’ number must be used additionally as the measure of the field diffusion. The character of wave processes in the core has been studied and the conditions of their essential influence on the field distribution have been established. That is shown that main criterion for estimation of the core filling up by the magnetic flux (i.e. for estimation of package using effectiveness) is the correlation between the dimension of cross section and the path of the wave run during the pulse duration. The criterion for observation only diffusion picture of the field propagation at the magnetic Reynolds’ number is the ratio . Under conditions when the wave phenomena play relatively small role the speed of the field diffusion instead of the velocity of the wave propagation must be used at the estimation of the package cross section effective usage